How long to treat osteoporosis - Adler, Robert A. (Henry Stewart Talks, 2024)
Osteoporosis, Anti-resorptive treatments, Osteonecrosis of the jaw, Atypical femoral fracture, Current RCT’s for long-term bisphosphonate treatment, Evidence for bisphosphonate drug holiday, Alternative treatments for oral bisphosphonates, Sequence of therapies matters, New treatment paradigms for osteoporosis